Penerapan Model Pembelajaran Jigsaw dengan Pendekatan Saintifik untuk Meningkatkan Pemahamana Konsep Matematis Siswa di MTs NW Lepak, Lombok Timur - Lastri, Windi AD; Hardiani, Nur (Mathematic Education Departement, State Islamic University of Mataram, 2025)
This study aims to determine the effect of the Jigsaw learning model with a scientific approach on the understanding of mathematical concepts of grade VII junior high school students of MTs NW Lepak on integer material. The type of research used is: quantitative with a posttest-only control group design. The sample was determined by the purposive sampling method. The data analysis technique in this study used the independent sample T-test with SPSS software. The results of the analysis showed that there was a significant effect of the application of the jigsaw learning model with a scientific approach on the understanding of mathematical concepts of grade VII A students of MTs NW Lepak.